PENERAPAN PEMBELAJARAN MODEL PBL (PROBLE BASED LEARNING)UNTUK MENINGKATKAN PRESTASI BELAJAR SUHU DAN KALOR - Abdul Salam (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2018)
The purpose of this action research is: (1) To determine the increase in student learning achievement after applied PBL Learning Model (Problem Based Learning) Subjects of Temperature and Heat in Class XI IPA3 Students of Sukodadi 1 High School 2018/2019 Academic Year (2) To determine the effect of applying model learning PBL (Problem Based Learning) towards increasing learning achievement Subject and Temperature Subjects in Class XI IPA3 Sukodadi High School 1 Year 2018/2019 Students. The procedure for classroom action research consists of three cycles and each cycle includes planning (action), action (action), observation (observation), and reflection (reflection). This research was conducted at Sukodadi 1 Public High School, with students of class XI IPA3 with 31 students, 17 women and 14 men. Data analysis using qualitative descriptive. The results showed that teacher activity was obtained. The first cycle (76.25%) increased in Cycle II (87.50%) experienced an increase in the third cycle (93.75%). Student activities in learning cycle I (76.79%) increased in cycle II (87.50%) and in cycle III (96.43%). Attitude skills obtained by the achievement of the first cycle (72.78%), increased in the second cycle (83.87%) and increased in the third cycle (87.90%). Pre test results Cycle I (48.4%), increased in the second cycle (74.2%) and increased again in the third cycle (93.5%). And the last is the response questionnaire of the first cycle students (70.97%), increased in the second cycle (80.65%) and experienced an increase in the third cycle (93.55%).